Endogenous trusted network architecture for intelligent sharing - Shaoyong GUO; Yuanyuan QI; Meiling DAI; Xuesong QIU; Feng QI; Ping ZHANG (Tongxin xuebao)
To address the needs of intelligent sharing of network resources,blockchain and artificial intelligence were integrated with the network,and an endogenous trusted resource intelligent sharing network architecture was proposed to make network asset sharing have endogenous trust.Based on distributed alliance blockchain,an integration mechanism of on-chain identification and off-chain resource was proposed to achieve credible management of network resources.Security and trusted sharing protocols for network data was designed to synchronize data consensus within the network.Based on smart contract,network resource scheduling and service composition methods were presented to achieve trusted service sharing.Finally,the proposed architecture was applied to decentralized scenarios such as domain name resolution,cross domain authentication,and virtual network operation.The proposed architecture realizes the integration of blockchain and network and supports the endogenous trusted sharing of network assets.